Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland - field photos and thin sections ... - Valdimarsdóttir, Iðunn Kara (Zenodo, 2023)
Fieldwork photos from Kverkfjöll, Iceland, since 2020 as a part of fieldwork-based master's thesis in geology, where a pillow lava and hyaloclastite formation was studied. Included are field photos and composited field photos, along with a map showing where said photos are. Also included are photomicrographs of thin sections, scanned and labeled photos of each thin section, and their rough position within each pillow crust sample. Please refer to the actual thesis for more information: Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfjöll region, Iceland (Valdimarsdóttir, 2023). ... : {"references": ["Valdimarsd\u00f3ttir, I. K. (2023). Origin, extent, and emplacement conditions of newly exposed pillow lavas in the Kverkfj\u00f6ll region, Iceland [Master's thesis, University of Iceland]", "Loftmyndir ehf. (2021). Grunnger\u00f0 Landuppl\u00fdsinga - Landuppl\u00fdsingag\u00e1tt [online map]. https://kort.lmi.is/mapview/?app=kort&l=is&c=609330,470991&z=13.6&ls=4858,1056,1053"]} ...